Clinical manifestations of 17 Chinese children with hereditary spherocytosis caused by novel mutations of the ANK1 gene and phenotypic analysis - Kang, Meiyun; Li, Huimin; Zhu, Jun; Zhu, Liwen; Hong, Yue; Fang, Yongjun (Frontiers in Genetics, 2023)
Background: Hereditary spherocytosis (HS) is an autosomal dominant (AD) and autosomal recessive (AR) disorder that is mostly caused by mutations of the erythrocyte membrane‐related gene ANK1. Methods: Clinical and genetic testing data of 17 HS children with ANK1 gene mutations were retrospectively collected. Clinical manifestations and phenotypic analysis of HS were summarized based on our experience and literature review. Results: A total of 17 mutations of the ANK1 gene were identified from 17 probands (12 sporadic cases and 5 familial cases), including 15 novel mutations and 2 previously reported ones. Among the 15 novel variants of ANK1, there were 4 nonsense mutations, 4 frameshift mutations, 3 splicing mutations, 3 missense mutations and 1 in-frame deletion of three amino acids. In the present study, HS patients with mutations in membrane binding domains had significantly lower hemoglobin (Hb) levels and higher total bilirubin (T-Bil) levels than those with mutations in regulatory domains. After reviewing and analyzing all available published reports of Chinese HS patients carrying ANK1 mutations in PubMed and Chinese journals, there were no significant differences in Hb, Ret and T-Bil between different mutation types or mutation regions. Conclusion: Mutations of the ANK1 can be inherited or de novo. Clinical manifestations of HS in children caused by ANK1 mutations are similar to those of other types of hemolytic anemia. Our report expands the mutation spectrum of HS, thus providing references for clinical management and genetic counseling of HS.